Minimize Customer Return by Using the Method of Quality Control Circle and Quality Loss Fuction: Study from PT Artha Food - Aris Tri Yulianto; Hana Catur Wahyuni (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
One of the keys to a company's success is quality control. PT Artha Food is a manufacturing industry engaged in the processing of cocoa powder trying to improve the quality of its products for customer satisfaction in accordance with the mission of the company, which is to become a world-class company focused on creating added value for consumers. But with the increase in company productivity, consumer complaints are also increasing. The biggest factor of consumer complaints is broken product when sent to the consumer. This resulted in increasing the return of products from consumers resulting in losses for the company because the rejeck product increases. The company will seek to minimize the return from consumers with existing resources so that consumer confidence increases and decreases the rejeck product. In this study, the method used in the quality control of product defects is the quality control circle used to analyze the damaged product. The method is integrated with quality loss fuction to know the producer loss factor By improving the quality with the quality control method circle the average broken product can be minimized from 295.45 kg / month before the improvement to 50 kg / month after the repair process.